REPRESENTATION OF INDONESIAN REVOLUTION IN POEM “RAPAT MENGGANYANG 7 SETAN” BY H.R. BANDAHARO - Artika, I Wayan; Kutha Ratna, I Nyoman; Darma Putra, I Nyoman; Weda Kusuma, I Nyoman (e-Journal of Linguistics, 2014)
This present study explores the representation of Indonesian Revolution in the poem “Rapat Mengganyang 7 Setan” written by H.R. Bandaharo. The meaning of the poem was revealed through the exploration of the reciprocal relationship between the speech delivered by President Soekarno and what was written by D.N. Aidit. The approach used was the qualitative one. The data were analyzed through parallel reading. The result of the study showed that the representation of the Indonesian Revolution through the themes and diction adopted from the expressions/slogans used during the revolution era. The reciprocal relationship between the poem “Rapat Mengganyang 7 Setan” and the speech delivered by President Soekarno and what was written by D.N. Aidit was based what is referred to as “Mukadimah Lekra” (Introduction to Lekra), “Konsepsi Kebudayaan Rakyat” (Conception of the People’s Culture), and “metode asas kombinasi 1-5-1” (Method of Combined Principle 1-5-1). Representation of the Indonesian Revolution in this literary work showed that literature was part of the political movement used to achieve what the Indonesian Revolution aimed at, namely, a community with justice and prosperity.
Keywords: representation, Indonesian Revolution, new historicism